Internal Factors Hindering the attainment of English Proficiency in ASEAN Common Competency Standard - Yunike Kurniarini (English Language and Education Spectrum, 2023)
This study is aimed to investigate internal factors hindering the attainment of English proficiency standards in the Common ASEAN Tourism Curriculum. The study was conducted to tourism students. The study used a descriptive qualitative method and the data were gained through questionnaires for the students in three sub-divisions; Hotel Accommodation, Food and Beverage, and Hotel Engineering. The findings showed that there are several internal factors that hinder the attainment of English proficiency standards. The internal factors include the lack of confidence to use English in interaction in the learning process and outside the class; the minimum ability to reach general English and English proficiency standards; the monotonous learning style in learning English; the lack of self-esteem in case of following the learning process by doing an assignment or practicing; the limited exploration and use of knowledge about English terms based on their subdivision; the lack of intrinsic motivation as the reason to improve their skill in English; the passive attitude by the students toward learning process of English subject. Keywords: English proficiency standard; Common ASEAN Tourism Curriculum; internal factors